Relating Career Orientation to Electrical and Electronics Technology Education Students’ Interest in and Attitude towards Technical Skill Acquisition in Southwest Nigeria - Shodeinde, Abidemi Olufemi; Efuwape, Bamidele Michael; Efuwape, Oluwabunmi Asake (Online Journal for TVET Practitioners, 2026)
In order to address the problem of graduates of skill-based programs joining the ranks of the unemployed due to a lack of necessary skills for employment or entrepreneurship, this study explored the relationship among Electrical and Electronics Technology Education students’ career orientation, interest, and attitude towards technical skill acquisition in universities in Southwest Nigeria. The study utilized a survey research design and collected data through a structured questionnaire. All 92 Electrical and Electronics Technology Education students in universities in Southwest Nigeria were purposively selected to participate in the study. Data collected were analyzed using Pearson Product Moment Correlation, t-test, and linear regression. The results revealed a significant positive relationship between career orientation and students’ interest and attitude towards technical skill acquisition. Also, there was no significant gender differences in students’ career orientation. Furthermore, career orientation significantly influenced students’ interest, and students’ interest had a significant effect on their attitude towards skill acquisition. The findings suggest the importance of providing qualitative career orientation programs to enhance students’ interest in and attitudes towards skill acquisition. The study concludes by recommending the consistent organization of career orientation programs, regular assessment of students’ interests, and positive reinforcement of students’ attitudes to improve skill acquisition in vocational programs.